EXECUTIVE INTERFERENCE IN THE ADMINISTRATION of JUSTICE at the ELECTION PETITION TRIBUNALS IN NIGERIA: Myths and Realities - Ugoh, Samuel C.; Ukpere, Wilfred (Journal of Economic Development, Environment and People, 2024)
This study focuses on the interface between the executive and the judiciary in the adjudication of electoral matters in Nigeria. Nigerians have had cause to reflect on access to justice, as well as the quality of justice that is available to individuals who seek justifiable remedies in the judicial system. Evidence shows that peoples’ aspirations for justice have been constantly frustrated by maladministration, unclear perverted electoral rules, irregularities and manipulations of parties’ primaries, corruption, and so on. The current paper argues that the causes are multi-dimensional, including unnecessary heating up of the body politics, political actors and the people, the inefficiency and ineffectiveness of the election management body, government interference, and so on. This study adopted a historical cum descriptive approach to political research, using secondary sources of information. The study applied both the systems approach and the theory of separation of powers, focusing on the judiciary deciding on disputes in conformity with the separation of powers principle. The study found that the nexus, which existed in both the executive and judiciary arms, has exposed some lapses among the judges that have been characterised by irregularities and manipulations. The study concluded that, unless the judicial system, including the election petition tribunals, are reconstituted, autonomised and free from executive interference, the people will never experience justice. The study recommends that the executive arm should operate within the confines of its responsibilities and allow the judiciary to carry out its duties promptly to win over the hearts and minds of the citizenry.